2021
DOI: 10.1212/cpj.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

Striking MRI Changes of Focal Cortical Dysplasia Over Time

Abstract: Purposeof review: Brain MRI findings of focal cortical dysplasia (FCD) can undergo dramatic changes over time, which may be related to long-term epilepsy or a combination of histopathologic changes that necessitate further investigation.Recent findings:We describe two cases of FCD Type IIb that initially displayed inconspicuous findings on MRI, however progressed to obvious signal changes on subsequent MRI 10-17 years later. Pathologic analysis indicates that the interval changes are likely attributed to react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, while the abnormality is too subtle to create pronounced MR signal alternations, there are no obvious contrast between the FCDs and surrounding tissues, that will not be detected on MRI (Figures 1 A, B, C, and D). Adina Achiriloaie et al (11) reported that conventional MRI sequences that shows to be negative at the the FCDs and the part of normal GM or WM. To a certain degree , it can magnify shows the lesion of FCDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the abnormality is too subtle to create pronounced MR signal alternations, there are no obvious contrast between the FCDs and surrounding tissues, that will not be detected on MRI (Figures 1 A, B, C, and D). Adina Achiriloaie et al (11) reported that conventional MRI sequences that shows to be negative at the the FCDs and the part of normal GM or WM. To a certain degree , it can magnify shows the lesion of FCDs.…”
Section: Discussionmentioning
confidence: 99%
“…1A–D ). Achiriloaie et al 11 reported that conventional MRI sequences that shows to be negative at the early stage might change and lesions may appear after years, especially whom has high seizure frequency. But it generally takes a long time.…”
Section: Discussionmentioning
confidence: 99%